GM-CSF Promotes the Expansion and Differentiation of Cord Blood Myeloid-Derived Suppressor Cells, Which Attenuate Xenogeneic Graft-vs.-Host Disease - Park, Mi-Young; Lim, Bang-Geul; Kim, Su-Yeon; Sohn, Hyun-Jung; Kim, Sueon; Kim, Tai-Gyu (Frontiers in Immunology, 2019)
Myeloid-derived suppressor cells (MDSCs) are increased in tumor patients. Studies have shown generation of MDSCs from human peripheral blood mononuclear cells (PBMCs) by various cytokine combinations. However, large scale expansion of human MDSCs has not been demonstrated or applied in clinic settings. We investigated which cytokine combinations among GM-CSF/SCF, G-CSF/SCF, or M-CSF/SCF efficiently expand and differentiate human MDSCs following culture CD34+ cells of umbilical cord blood (CB). GM-CSF/SCF showed the greatest expansion of MDSCs. Up to 108 MDSCs (HLA-DRlowCD11b+CD33+) could be produced from 1 unit of CB following 6 weeks of continuous culture. MDSCs produced from culture of CD34+ cells with GM-CSF/SCF for 6 weeks had the greatest suppressive function of T cell proliferation and had the highest expression of immunosuppressive molecules including iNOS, arginase 1 and IDO compared to those differentiated with G-CSF/SCF or M-CSF/SCF. MDSCs secreted IL-10, TGB-β, and VEGF. The infusion of expanded MDSCs significantly prolonged the survival and decreased the GVHD score in a NSG xenogeneic model of GVHD. Injected MDSCs increased IL-10 and TGF-β but decreased the level of TNF-α and IL-6 in the serum of treated mice. Notably, FoxP3 expressing regulatory T (Treg) cells were increased while IFN-γ (Th1) and IL-17 (Th17) producing T cells were decreased in the spleen of MDSC treated mice compared to untreated GVHD mice. Our results demonstrate that human MDSCs are generated from CB CD34+ cells using GM-CSF/SCF. These MDSCs exhibited potent immunosuppressive function, suggesting that they are useable as a treatment for inflammatory diseases such as GVHD.